Hospice and palliative care clinicians' perceptions of posttraumatic stress disorder at end-of-life in military veterans. (4th July 2022) - Pless Kaiser, Anica; O'Malley, Kelly; Moye, Jennifer; Etchin, Anna G.; Korsun, Lynn; Weiskittle, Rachel; Bashian, Hannah; Kemp, Katherine; Sager, Zachary S.
Abstract : At the end of life, individuals may re-engage with earlier life trauma as they reflect on life experiences and confront their mortality. As such, posttraumatic stress disorder (PTSD) symptoms at the end of life may worsen the quality of death experience. This is a concern for military veterans, who tend to have more trauma exposures and higher rates of PTSD, and particularly for veterans receiving care in rural areas where access to PTSD specialty services is limited. To better understand this issue, we conducted 10 focus groups with clinicians serving veterans in rural communities across five U.S. states. The aims of this project were to evaluate: (1) do hospice and palliative care providers/staff observe PTSD symptoms in veterans at the end of life? (2) if so, how are symptoms similar to and different from existing DSM-5 criteria for PTSD? We used qualitative content analysis with mixed deductive and inductive approaches to code 151 anonymized statements. Analyses found descriptions of PTSD symptoms aligned broadly with existing diagnostic nomenclature, but descriptions revealed specific presentations relevant to the end of life setting such as resistance to care, agitation, restlessness, and effects of delirium. In addition, some veterans expressed pride in service and openness to discussing military experiences. Further, clinicians noted that PTSD symptoms were relevant to family dynamics. Future research should further characterize these symptom differences through direct patient assessment and develop resources to improve quality of death experience for veterans with PTSD symptoms.